Complex temperature mosaics across space and time in estuaries: implications for current and future nursery function for Pacific salmon - Gross, Phoebe L.; Gan, Julian C.L.; Scurfield, Daniel J.; Frank, Cory; Frank, Cedar; McLean, Caelan; Bob, Chris; Moore, Jonathan W. (Frontiers in Marine Science, 2023)
Water temperature is a key dimension of estuaries that can influence important biological processes including organismal growth, survival, and habitat use. For example, juvenile Pacific salmon rely on temperature-mediated growth opportunities in estuaries during seaward migration in the spring and summer. However, oncoming climate change is warming estuary temperatures and transforming growth potential. Yet, it is likely that estuary water temperatures are complex and dynamic across space and time. Here we investigated spatial and temporal patterns of water temperature across two contrasting estuaries on Vancouver Island, BC, and used these data to simulate juvenile Chinook salmon growth potential under both present conditions and a simplified scenario of climate warming. Summer temperatures were warmer and more spatially homogeneous across the Englishman River estuary relative to the Salmon River estuary. Within each system, temperature was variable across habitats and sites, appearing to be driven by a combination of local climate, river and ocean temperatures, tidal fluctuations, and habitat features. This shifting mosaic of temperatures generated a complex portfolio of growth opportunities for juvenile Chinook salmon. There were broad patterns of increasing growth potential across both systems as temperatures warmed in early summer. However, excessively hot late summer temperatures drove steep declines in growth potential across the Englishman River estuary, while positive trends continued through August in the Salmon River estuary. A simple climate change scenario revealed that estuaries and habitats may have differing vulnerabilities to increasing temperatures—with climate warming, favorable growth opportunities were even more constricted to early summer in the Englishman River estuary, but expanded across most habitats and times in the Salmon River estuary given lower baseline temperatures and higher habitat complexity. Collectively, this work underscores the importance of habitat complexity and local climate for maintaining diverse growth opportunities across estuaries, which may confer resilience to the nursery function of estuaries as temperature mosaics warm.